2021
DOI: 10.1681/asn.2020040423
|View full text |Cite
|
Sign up to set email alerts
|

Tubuloglomerular Feedback Synchronization in Nephrovascular Networks

Abstract: To perform their functions, the kidneys maintain stable blood perfusion in the face of fluctuations in systemic BP. This is done through autoregulation of blood flow by the generic myogenic response and the kidney-specific tubuloglomerular feedback (TGF) mechanism. The central theme of this paper is that, to achieve autoregulation, nephrons do not work as single units to manage their individual blood flows, but rather communicate electrically over long distances to other nephrons via the vascular tree. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 111 publications
0
15
0
Order By: Relevance
“…Macula densa cells will release ATP, with subsequent adenosine formation through extracellular ATP degradation. Adenosine stimulates the A1 adenosine receptors to mediate glomerular afferent arteriole constriction, which can be modulated by the renin-angiotensin system, resulting in a corresponding reduction in GFR in the surrounding nephron network beyond each nephron [20]. Any reduction in reabsorptive activity of the PT epithelial cells in AKI leading to an increase in solute delivery downstream to the macula densa is Transmission EM of a dog's proximal convoluted tubules after 1 h of haemorrhagic shock.…”
Section: Histological and Physiological Basis To Target The Proximal ...mentioning
confidence: 99%
“…Macula densa cells will release ATP, with subsequent adenosine formation through extracellular ATP degradation. Adenosine stimulates the A1 adenosine receptors to mediate glomerular afferent arteriole constriction, which can be modulated by the renin-angiotensin system, resulting in a corresponding reduction in GFR in the surrounding nephron network beyond each nephron [20]. Any reduction in reabsorptive activity of the PT epithelial cells in AKI leading to an increase in solute delivery downstream to the macula densa is Transmission EM of a dog's proximal convoluted tubules after 1 h of haemorrhagic shock.…”
Section: Histological and Physiological Basis To Target The Proximal ...mentioning
confidence: 99%
“…Such interactions are proven to play a critical role in kidney function and can lead to complex co-operative dynamics and synchronization between nephrons. Adaptive synchronization across the renal microvascular network would increase the efficiency and dynamic range of autoregulation by engaging more preglomerular resistance ( Marsh et al, 2019 ; Zehra et al, 2021 ), preventing transmission of high systemic pressure to the glomeruli, which could lead to progressive glomerular and vascular injury. In addition, long-distance synchronization would argue strongly that renal autoregulation is a distributed process that can ensure an optimized oxygenation-perfusion matching and adjust to various internal or environmental conditions ( Sosnovtseva et al, 2007 ; Mitrou et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of the complexity of the kidney’s microvascular physiology and anatomy has altered the idea that each nephron is responsible for its own autoregulation. We and others have suggested that nephrovascular units (NVUs), which consist of a nephron and its afferent and efferent arteriole, communicate with each other in a network, and explain renal autoregulation and perfusion in the kidneys better [ 89 ]. TGF generates oscillations within each NVU, and oscillatory systems with similar frequencies can entrain and become synchronized [ 90 , 91 , 92 ].…”
Section: Alternative Explanations For the Beneficial Effects Of Sglt-...mentioning
confidence: 99%
“…TGF generates oscillations within each NVU, and oscillatory systems with similar frequencies can entrain and become synchronized [ 90 , 91 , 92 ]. This synchronization among NVUs, which increases RBF autoregulation efficacy, could prevent a discrepancy between metabolic demand and oxygen delivery as each NVU’s tubule is perfused by four or five nearby NVUs [ 89 ]. Consequently, one theory explaining the renoprotective effects of SGLT2 inhibitors is that they can enhance network dynamics among NVUs to activate the TGF response sustainably.…”
Section: Alternative Explanations For the Beneficial Effects Of Sglt-...mentioning
confidence: 99%
See 1 more Smart Citation